2014
DOI: 10.3390/ijms15058280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Soybean Koji Extract on Glucose Utilization and Adipocyte Differentiation in 3T3-L1 Cells

Abstract: Adipocyte differentiation and the extent of subsequent fat accumulation are closely related to the occurrence and progression of diseases such as insulin resistance and obesity. Black soybean koji (BSK) is produced by the fermentation of black soybean with Aspergilllus awamori. Previous study indicated that BSK extract has antioxidative and multifunctional bioactivities, however, the role of BSK in the regulation of energy metabolism is still unclear. We aimed to investigate the effect of glucose utilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…It has been reported that delipidated soybean or anthocyanin derived from purple sweet potato inhibits lipogenesis by suppressing the expression of ACC and FAS, which play major roles in lipogenesis (Hwang et al, 2011;Lee et al, 2011). Another study demonstrated that BBC ethanol extract showed inhibitory effects on PPARγ but not on SREBP in 3T3-L1 adipocytes (Huang, Huang, Hou, Chi, & Huang, 2014). On the other hand, there had been reports of the insulin-like effect of C3G by increasing the activity of PPARγ in human omental adipocytes, showing that there might be a conflict in the role of anthocyanin on PPARγ (Scazzocchio et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that delipidated soybean or anthocyanin derived from purple sweet potato inhibits lipogenesis by suppressing the expression of ACC and FAS, which play major roles in lipogenesis (Hwang et al, 2011;Lee et al, 2011). Another study demonstrated that BBC ethanol extract showed inhibitory effects on PPARγ but not on SREBP in 3T3-L1 adipocytes (Huang, Huang, Hou, Chi, & Huang, 2014). On the other hand, there had been reports of the insulin-like effect of C3G by increasing the activity of PPARγ in human omental adipocytes, showing that there might be a conflict in the role of anthocyanin on PPARγ (Scazzocchio et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Bioactive compounds from soybeans and pulses have been investigated for their efficacy in improving glucose utilization and insulin sensitivity via increasing GLUT4 gene expression and/or plasma membrane levels. Huang et al [ 49 ] used black soybean koji (a fermented black soybean product) to prepare an extract for treating 3T3-L1 preadipocytes. Preadipocytes are commonly used in insulin resistance studies to determine effects on adipogenesis and related processes, such as glucose uptake [ 50 , 51 ].…”
Section: The Proposed Mechanisms Of Action For Reduction Of Insulimentioning
confidence: 99%
“…Insulin resistance was induced in the preadipocytes by treating with dexamethasone and insulin for 60 h (eight days is required to obtain mature adipocytes under the culture conditions), a method shown to promote insulin resistance in this cell line [ 52 ]. The black soybean koji extract increased protein levels of GLUT4 in a dose-dependent manner from 25 to 200 μg/mL compared with the vehicle treatment in the preadipocytes [ 49 ]. Furthermore, the highest concentration of black soybean koji extract (200 μg/mL) significantly increased glucose utilization in the preadipoctyes compared with the vehicle treatment.…”
Section: The Proposed Mechanisms Of Action For Reduction Of Insulimentioning
confidence: 99%
See 1 more Smart Citation
“…NADPH derived from glucose-6-phosphate dehydrogenase, the limiting enzyme of HMP, is known to increase the levels of cellular ROS production by NADPH oxidase. Furthermore, excessive ROS generation is associated with increased lipid accumulation during adipocyte differentiation ( 33 , 34 ). Previous studies reported excessive differentiation of 3T3-L1 cells induced by transition metals (Cu 2+ or Fe 2+ ), due to increased expression of adipogenic transcriptional factors related to the NADPH-dependent H 2 O 2 -generating system ( 35 ).…”
Section: Discussionmentioning
confidence: 99%